Where's my hero? ebook - Kleypas, Lisa (2009)
Dear Avon Books, Where are my heroes? Whenever I'm reading a book by one of my favorite authors I find I'm falling for the wrong guy — not the hero, but the other man — and what I really want is for him to have his own story. Like Jake Linley, from Someone to Watch Over Me by Lisa Kleypas...that doctor could sit by my bedside if I ever got sick. And Ned Blydon in Splendid by Julia Quinn...he makes me want to learn to waltz! I never thought living in a drafty castle would be much fun until Simon of Ravenswood in Master of Desire by Kinley MacGregor came along. Anyway, I just wanted to let you know that these are my men — when do they get their stories? Sincerely, A Romance Fan Some books are so special that there is more than one hero to love, but only a single story is told. So if you find yourself asking, "Where is my hero?" you'll discover the answer right here in this delicious collection by New York Times bestseller Lisa Kleypas, New York Times bestseller Julia Quinn and USA Today bestseller Kinley MacGregor.